The Importance of Gender-Based Standard Operating Procedures for Disaster Management in East Java - Achmad, Zainal Abidin; Nuryananda, Praja Firdaus; Haq, Jelita Arinal; Budiwitjaksono, Gideon Setyo; Agustina, Zalfa Nurrahmah (Institut Teknologi Sepuluh Nopember, 2024)
Disaster management addresses gender inequality by mitigating adverse effects on women. Involving women in disaster risk reduction is crucial, but their participation is often insufficient, leading to inadequate attention to their specific needs. In Indonesia, where women make up over half the population, their involvement in disaster management is essential. This study explores women’s disaster risk mitigation strategies and emphasizes gender-responsive disaster management approaches. Following the 2021 Mount Semeru eruption, research in East Java revealed gender-sensitive disaster management deficiencies. Traditional methods often fail to support women and children who are particularly vulnerable. The study highlights the importance of education, training, and gender-sensitive disaster management policies. Using a phenomenological approach, the study conducted direct observations, in-depth interviews, and focus groups. It identified 24 significant obstacles in gender-based disaster management, such as inadequate casualty statistics and the lack of gender-specific infrastructure in refugee camps. The research underscores the need for gender-specific standard operating procedures (SOPs) to safeguard women and children's well-being during and after disasters. Enhancing education and capacity-building in vulnerable villages is also crucial for effective disaster mitigation. To improve disaster resilience, it is essential to integrate women into the disaster management framework, acknowledging their specific needs and harnessing their capabilities.